Immediate improvement of intraoperative monitoring signals following CSF release for cervical spine stenosis: Case report. (July 2018) - Pennington, Zach; Zygourakis, Corinna; Ahmed, A. Karim; Kalb, Samuel; Zhu, Alex; Theodore, Nicholas
Highlights: Cervical spondylotic myelopathy is characterized by conduction block. In animal models, compression decreases cord perfusion and alters CSF flow. Improved conduction seen post-decompression may be due to improved cord perfusion. Abstract: Cervical spondylotic myelopathy (CSM) is a degenerative pathology characterized by partial or complete conduction block on intraoperative neuromonitoring. We describe a case treated using osseoligamentous decompression and durotomy for cerebrospinal fluid (CSF) release. Intraoperative monitoring demonstrated immediate signal improvement with CSF release, suggesting that clinical improvement in CSM may result from resolution of CSF flow anomalies.